Pesticides and global health - Dowdall, Courtney Marie, author.
1 online resource
Keywords: "This concise, accessible introduction to understanding agricultura chemicals and public health combines a broad synthesis on a global scale with rich ethnographic narratives on a human scale. Drawing on epidemiology, policy analysis, and social science research on the global commodity chain, the authors describe the system of global agrochemical dependence that constitutes a major threat to human health. Then they draw readers into the luch mountainsides of highland Guatemala, telling personal stories of farmers, their experiences with public health programs, their struggles against agrichemical dependence, and their innovations in sustainable argriculture. Finally, they show how this kind of qualitative, multi-level analysis holds practical lessons for public health. This engaging, brief text is an ideal supplement for courses in global health, introducing students to key concepts with broad coverage and engrossing ethnographic detail."--Provided by publisher.